The Organic Waste Processing as an Alternative Energy Source of Bio- Briquettes For Kedung Klinter Citizen Surabaya (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Waste that is not managed and utilized can be a big problem, but on the one hand, if it can be managed well, then waste can bring blessings and benefits to society in realizing a circular economy. Therefore, educational and community empowerment activities are needed in utilizing and managing organic waste as a new and renewable energy source for bio briquettes. The aim of this community service is to provide education to community members to utilize organic waste to become an alternative energy source, bio briquettes. This event was attended by no less than 25 environmental assistants representing RW in the Kedung Klinter area, Kedungdoro Village, Tegalsari District, Surabaya. This activity methods are packaged in the form of education in lectures, interactive questions and answers with participants and practice of making bio-briquettes. The response from the Village Head and residents was very positive and enthusiastic. Participants open their minds and increase their knowledge and skills regarding the management and utilization of organic waste into charcoal briquettes from organic waste. The results of this activity are appropriate technological equipment, Briquette Printing Equipment and Briquette Stoves.     The conclusion of this activity is that there is an increase in community knowledge about the process of making bio briquettes, there is still a need for several improvements, innovations, developments and ongoing efforts to improve the quality of community briquette printing results into more prospective products both in terms of briquette printing tools, briquette stoves and material composition. making charcoal briquettes.